2002
DOI: 10.2337/diacare.25.11.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Cystatin C for the Estimation of Glomerular Filtration Rate in Type 1 Diabetes

Abstract: 1OBJECTIVE -Assessment and follow-up of early renal dysfunction is important in diabetic nephropathy. Plasma creatinine is insensitive for a glomerular filtration rate (GFR) Ͼ50 ml/min and creatinine clearance is unwieldy and subject to collection inaccuracies. We aimed to assess the reproducibility, reliability, and accuracy of plasma cystatin C as a measure of GFR ranging from normal to moderate impairment due to type 1 diabetes in the presence of a normal plasma creatinine concentration. RESEARCH DESIGN AND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
0
5

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 26 publications
5
108
0
5
Order By: Relevance
“…38 Studies comparing urinary and plasma clearance of either iothalamate or iohexol show high agreement, although some studies showed that plasma clearance slightly overestimates urinary clearance at lower levels of GFR (Table 5). 17,34 In studies of repeated measurements of plasma clearance of iothalamate or iohexol, the coefficient of variation ranged from 5.6 to 11.5%, 37,39,42,43 similar to the variation observed with urinary clearance reported above. More studies are necessary to determine the precision of these methods.…”
Section: Bsc Urinarymentioning
confidence: 52%
“…38 Studies comparing urinary and plasma clearance of either iothalamate or iohexol show high agreement, although some studies showed that plasma clearance slightly overestimates urinary clearance at lower levels of GFR (Table 5). 17,34 In studies of repeated measurements of plasma clearance of iothalamate or iohexol, the coefficient of variation ranged from 5.6 to 11.5%, 37,39,42,43 similar to the variation observed with urinary clearance reported above. More studies are necessary to determine the precision of these methods.…”
Section: Bsc Urinarymentioning
confidence: 52%
“…The error induced by this phenomenon is particularly relevant at low levels of GFR. No difference was found between the plasma clearance of 51 Cr-EDTA and of 99m Tc-DTPA (4,5).…”
Section: Measurement Of Glomerular Filtration Ratementioning
confidence: 83%
“…Several compounds labeled with radioisotopes have been used for the assessment of GFR. Among these are 125 I-iothalamate, 99m Tc-diethylenethiaminepenta-acetic acid ( 99m Tc-DTPA) and 51 Cr-ethylenediaminetetra-acetic acid ( 51 Cr-EDTA). All these compounds have a low molecular weight and their plasma protein binding and extrarenal elimination are negligible.…”
Section: Measurement Of Glomerular Filtration Ratementioning
confidence: 99%
See 2 more Smart Citations